Pendekatan Behaviorial Operant Conditioning dalam Membentuk Perilaku Hidup Bersih dan Sehat Terhadap Santri Pondok Pesantren Nashrus Sunnah Kelurahan Banjarejo Kota Madiun - Qoni’ah Qoni’ah; Nuril Endi Rahman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Islamic boarding schools are a place to gain knowledge, not only religious and formal knowledge but also the students are taught various things, one example is learning to be aware of maintaining cleanliness. The background to this research is the results of observations that show that the girls' dormitory environment is less clean, resulting in health problems such as skin diseases and poor personal hygiene among students. This research aims to examine the effectiveness of the behavioral operant conditioning approach in forming clean and healthy living behavior (PHBS) in students at the Nashrus Sunnah Islamic Boarding School in Banjarejo Village, Madiun City. This research uses a qualitative method with a naturalistic approach, involving observation, interviews and documentation as data collection techniques, and data analysis is carried out inductively with triangulation of data sources for validity. The research results show that through the operant conditioning approach implemented by the health task force and academics, students show an increase in clean and healthy living behavior. Habits such as throwing rubbish in its place, maintaining personal hygiene, and cleaning the dormitory environment have become new habits that are implemented in a disciplined manner. This approach is also followed by giving rewards and punishments as a form of reinforcement to maintain the consistency of the new habit. In conclusion, the behavioral operant conditioning approach is effective in increasing PHBS in Islamic boarding school environments, showing significant changes in the behavior and motivation of students in maintaining cleanliness and health.